Are validated outcome measures used in distal radial fractures truly valid?: A critical assessment using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. Issue 4 (April 2016) - Kleinlugtenbelt, Y. V.; Nienhuis, R. W.; Bhandari, M.; Goslings, J. C.; Poolman, R. W.; Scholtes, V. A. B.
Abstract : Objectives: Patient-reported outcome measures (PROMs) are often used to evaluate the outcome of treatment in patients with distal radial fractures. Which PROM to select is often based on assessment of measurement properties, such as validity and reliability. Measurement properties are assessed in clinimetric studies, and results are often reviewed without considering the methodological quality of these studies. Our aim was to systematically review the methodological quality of clinimetric studies that evaluated measurement properties of PROMs used in patients with distal radial fractures, and to make recommendations for the selection of PROMs based on the level of evidence of each individual measurement property. Methods: A systematic literature search was performed in PubMed, EMbase, CINAHL and PsycINFO databases to identify relevant clinimetric studies. Two reviewers independently assessed the methodological quality of the studies on measurement properties, using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. Level of evidence (strong / moderate / limited / lacking) for each measurement property per PROM was determined by combining the methodological quality and the results of the different clinimetric studies. Results: In all, 19 out of 1508 identified unique studies were included, in which 12 PROMs were rated. The Patient-rated wrist evaluation (PRWE) and the Disabilities of Arm, Shoulder and Hand questionnaire (DASH) were evaluated on most measurement properties. The evidence for the PRWE is moderate that its reliability, validity (content and hypothesis testing), and responsiveness are good. The evidence is limited that its internal consistency and cross-cultural validity are good, and its measurement error is acceptable. There is no evidence for its structural and criterion validity. The evidence for the DASH is moderate that its responsiveness is good. The evidence is limited that its reliability and the validity on hypothesis testing are good. There is no evidence for the other measurement properties. Conclusion: According to this systematic review, there is, at best, moderate evidence that the responsiveness of the PRWE and DASH are good, as are the reliability and validity of the PRWE. We recommend these PROMs in clinical studies in patients with distal radial fractures; however, more clinimetric studies of higher methodological quality are needed to adequately determine the other measurement properties. Cite this article: Dr Y. V. Kleinlugtenbelt. Are validated outcome measures used in distal radial fractures truly valid?: A critical assessment using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. Bone Joint Res 2016;5:153–161. DOI: 10.1302/2046-3758.54.2000462.